LE FUTUR EST DANS LE PASSÉ : LA CONCEPTION ORIGINALE DU TEMPS AFRICAIN SELON JOHN MBITI - MOUNGA, Bauvarie (Studia Universitatis Babeș-Bolyai Philosophia, 2015)
The Kenyan philosopher John Mbiti highlights an original concept of time through his works: Religions et philosophie africaines (1969) and L’Eschatologie du Nouveau Testament en contexte africain : une étude de la rencontre de la théologie du Nouveau Testament et des concepts traditionnels africains (1971). Indeed, he uses the concepts of Western philosophy to share with us the African apprehension of time. This paper assumes that the future is in the past in African societies. So it is for us to help in the understanding of this statement and see to what extent the thought of Mbiti can evolve work on philosophy and particularly African philosophy. In this perspective, our paper will be structured in four parts: the specificities of the African, the analysis of the three time dimensions, the criticism vis-à-vis the Mbiti’s study and attempts of improvement and reformulation thought the Kenyan philosopher.